1996
DOI: 10.1016/0959-8049(96)00112-8
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of androgen receptors in breast cancer and their relation to histological and cell biological parameters

Abstract: To analyse the clinical significance of the presence of androgen receptors (AR) in breast carcinomas, clinical and histological parameters of 153 primary breast carcinomas (median follow-up 46 months) were examined. Oestrogen (ER) and progesterone receptor (PR) levels were determined in cytosol preparations using enzyme immunoassay assays and in cryostat sections by immunohistochemistry. AR and Ki-67 levels were only determined immunohistochemically. Data were analysed by uni- and multivariate models. 94/153 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
88
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 22 publications
12
88
1
2
Order By: Relevance
“…18,19,29,30,32,36,37 However, our study could not demonstrate significant association of androgen receptor with age, tumor size, lymph node status or basal-like phenotype. Its frequency of expression in our series is comparable with results of Collins et al, 38 and raises the possibility of targeted therapy to androgen receptor expressing tumors.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…18,19,29,30,32,36,37 However, our study could not demonstrate significant association of androgen receptor with age, tumor size, lymph node status or basal-like phenotype. Its frequency of expression in our series is comparable with results of Collins et al, 38 and raises the possibility of targeted therapy to androgen receptor expressing tumors.…”
Section: Discussioncontrasting
confidence: 77%
“…In these studies, its expression by immunohistochemistry was shown to be associated with a good prognosis in ER/PRnegative cancers. 23 Conversely, loss of androgen receptor was associated with a poor prognosis in lymph node-positive ER/PR/Her2-negative breast cancers. 24 These findings are consistent with cellbased assays, where androgen receptor activation with the agonist 5-dihydrotestosterone 25 or dehydroepiandrosterone sulfate 26 inhibits cell growth in androgen receptor-positive breast cancer cell lines, suggesting initiation of a growth inhibitory signal in 27 have found that androgen receptor function can be inhibited by low doses of progestins, which are similar to doses achieved in the serum of women on hormone replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AR expression has been found in 84% (47) to 91% (48) of clinical breast cancers, and associated with ER status, but has also been found in 49% of ER-negative tumors (49). Patients with tumors that coexpress AR with ER and progesterone receptor have shown longer disease-free survival (DFS) than patients whose tumors were negative for all three receptors (48), but AR protein levels have also served as an independent predictor of axillary metastases in multivariate analysis (47) Furthermore, AR expression has correlated with decreased histopathologic grade, greater age, and postmenopausal status, but also lymph node -positive status (50). In AR-positive/ER-negative tumors, AR expression again associated with positive and negative indicators/outcome such as increased age, postmenopausal status, and longer DFS but also tumor grade, tumor size, and HER-2/neu overexpression (49).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective clinical studies showed that AR by IHC adds prognostic information beyond the established clinicopathologic parameters in all patient groups and in patients with early-stage ER-positive breast cancer (9,13,14). Tumors coexpressing AR and ER are smaller, have lower Nottingham grade and low proliferative index (14), lymph node involvement is less frequent, and they are more likely to be found in postmenopausal women (4). However, the clinical significance of AR in patients with ER-negative breast cancer is less clear.…”
Section: Introductionmentioning
confidence: 99%